Framework of the Language Learning Environment for Assisting Foreigners in Learning Croatian (AFILC) - Posavec, Kristina; Mikelić Preradović, Nives; Kišiček, Sanja (2011)
The goal of this paper is to present the development framework of the interactive multimedia project AFILC (Assisting Foreigners in Learning Croatian). The purpose of the AFILC is to develop language learning materials that will motivate foreigners to learn the Croatian language and help them cope with its grammatical richness. Interesting graphics, motivating user-friendly interface, educational character and interactivity are the characteristics that will enhance the process of mastering the Croatian language for foreigners. In the AFILC the users will be able to almost completely control and manage the process of learning at their own pace.
Projekt MZOS
Projekt MZOS
ENG